2017
DOI: 10.1111/trf.14248
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheter placement in coagulopathic patients: risk factors and incidence of bleeding complications

Abstract: BACKGROUND Central venous catheters are frequently inserted into patients with coagulation disorders. It is unclear whether preprocedural correction of hemostasis is beneficial. We determined the incidence of bleeding complications after central venous catheter placement in patients who had severe coagulopathy and identified potential risk factors for bleeding. STUDY DESIGN AND METHODS The MEDLINE and Cochrane Library databases were systematically searched through November 2015. To be included, articles must h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 54 publications
5
56
0
1
Order By: Relevance
“…This is in line with earlier results concerning both SAE reporting and clinical bleeding. 1,7,30 Also, we have shown that the way of reporting bleeding assessment is often limited. The lack of this essential information reduces the validity and hampers the reproducibility of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with earlier results concerning both SAE reporting and clinical bleeding. 1,7,30 Also, we have shown that the way of reporting bleeding assessment is often limited. The lack of this essential information reduces the validity and hampers the reproducibility of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…P atients with a low platelet count (thrombocytopenia) have an increased risk of both spontaneous and post-procedural bleeding. 1,2 Platelet transfusions are therefore recommended in various guidelines, [3][4][5] either when the platelet count drops below a certain threshold or prior to invasive procedures. The clinical studies forming the basis of these guidelines are known to be of low quality, [3][4][5][6] essentially reducing the value of transfusion guidelines to the quality level of expert opinion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…63,71,75 Major bleeding from CVC insertion is uncommon, even in patients who have thrombocytopenia and coagulation disorders. 76 Catheter placement can be performed safely with platelet counts of 20 3 10 9 /L or greater. 77 This complication is less likely to be a problem in patients with SCD, who usually have normal or increased platelet counts.…”
Section: Catheter Complications and Carementioning
confidence: 99%
“…For example, a recent systematic review was unable to identify values of coagulation tests, including the prothrombin time (PT) or international normalized ratio, required to support safe central venous catheterization. 1 It is also well recognized that the PT and activated partial thromboplastin time provide only a very limited assessment of hemostatic status, for several reasons: these include that the PT and activated partial thromboplastin time measure the time taken for a clot to form which occurs when only 5% of total thrombin generation (TG) has occurred, they reflect only the procoagulant factors and are unaffected by the levels of natural anticoagulants, they are insensitive to modest but clinically relevant low levels of procoagulant factors, and finally they are poor at identifying a prothrombotic state. [2][3][4][5] Despite being some of the most frequently ordered hematology investigations in hospital practice, conventional coagulation tests may therefore have limited predictive value for clinical bleeding and the safety of invasive procedures, 6 and their role in indicating a need for plasma transfusion in nonbleeding patients remains unclear.…”
mentioning
confidence: 99%